Some problems of development of administrative justice in Ukraine - Компанієць, І. М.; Чиркін, А. С. (Theory and practice of jurisprudence, 2016)
The article contains analyses of legislation, scientific views and judiciary practice concerning the main problems of administrative justice. The approaching to solving the specific problems are suggested according to results of the research